Vertical axis wind machine tower of fractal structure - ZHANG JUNWEI; LI CHUN; MIAO WEIPAO; YANG YANG; ZHANG WANFU; YANG JUN; YE KEHUA (2017)
The invention relates to a vertical axis wind machine tower of a fractal structure. The vertical axis wind machine tower comprises a cylindrical thin-wall tower body, an upper supporting frame, a lower supporting frame and blades. Fractal holes are evenly distributed in the positions, between the upper supporting frame and the lower supporting frame, around the tower body in an arrayed manner, so that one part of wind of the upstream blades penetrates the fractal holes to damage falling-off vortex of the upstream blades of the tower and wake flow vortex of the downstream portion of the tower, and therefore vibration of the tower, interaction between the blades and the tower and the agitating function of the tower on the downstream blades are weakened. Reinforcing joints are arranged between the upper-layer fractal hole structure and the lower-layer fractal hole structure and used for overcoming reduction of the tower strength caused by the fractal holes. According to the vertical axis wind machine tower, inte